Polymorphism and Structure-Property Relations - Bernstein, Joel (Polymorphism in Molecular Crystals, 2020)
Chapter 6 deals with the connection between the structure and properties of solids as revealed and studied in polymorphic systems. The subject is divided into properties that depend on the one hand on the bulk—that is, the three-dimensional arrangement of the molecules and the interactions among them—and on the other hand the consideration of the crystal as an “oriented gas” serving to act as a matrix for the molecules to permit the study of molecular properties. Among the properties described in the former category are electrical conductivity, organic magnetic materials, photovoltaicity and photoconductivity, second harmonic generation, chromoisomerism, photochromism, thermochromism and mechanochromism, and the mechanosalient effect. The latter category includes a discussion of spectroscopic studies (infrared, Raman, and ultraviolet/visible), excimer phenomena, time-resolved studies of excited states, photochemical reactions and thermal and gas reactions, along with a variety of emission phenomena. The chapter closes with a brief survey of rapidly emerging and developing high pressure studies